Hubungan antara Empati dengan Perilaku Prososial terhadap Mahasiswa Etnis Pinaesaan Salatiga - Masinambouw, Nadia Liliana Sharon; Prasetya, Berta Esti Ari (Widya Cakra: Journal of Psychology and Humanities, 2022)
Pinaesaan is a student association from North Sulawesi in Salatiga. One of the ethnicities from North Sulawesi is Minahasa which has a slogan as their characteristic "Si Tou Timou Tumou Tou" or "humans are human beings", which means each individual applies prosocial behavior to each other. Prosocial behavior is related to empathy in each individual. The purpose of this study was to determine the relationship between empathy and prosocial behavior towards students of the Pinaesaan in Salatiga. This study uses quantitative methods with 151 students as participants. The sampling technique in this research is accidental sampling. The measurements of this study were used IRI (Interpersonal, Reactivity, Index) scale for empathy and PTM-R (Prosocial Tendencies Measure-Revised) scale for prosocial behavior. Reliability in this scale using Alpha Cronbach reliability coefficient of 0,868 (?=0,868). The relationship between empathy and prosocial behavior used Pearson Product Moment correlation. The correlation coefficient obtained is 0.229 with a significance value of p = 0.002 (p<0.05) which means that there is a positive significance relationship between empathy and prosocial behavior in students of the Pinaesaan ethic group in Salatiga.